Proceedings of the 2nd International Conference on Education, Language and Art (ICELA 2022) 2023
DOI: 10.2991/978-2-38476-004-6_26
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of COVID-19 on Chinese Students Studying Abroad

Abstract: The COVID-19 pandemic has led to a sharp deterioration of Chinese international students' social and psychological environment. Social isolation, public media opinion, school blockades, and social unrest have brought huge psychological impacts to Chinese students. Moreover, the education sector has unaddressed the difficulties and worries faced by Chinese students considering learning overseas during the pandemic. Chinese students are prone to homesickness and loneliness since they spend much time alone living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…J. Yang (2022) assessed the impact of COVID-19 on students studying abroad, with a focus on Chinese international students. He showed that Chinese international students faced significant levels of anxiety in the early stages of the COVID-19 pandemic, which was primarily caused by preconceived fear of COVID-19 and contradictory information often received from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…J. Yang (2022) assessed the impact of COVID-19 on students studying abroad, with a focus on Chinese international students. He showed that Chinese international students faced significant levels of anxiety in the early stages of the COVID-19 pandemic, which was primarily caused by preconceived fear of COVID-19 and contradictory information often received from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…J. Yang (2022) assessed the impact of COVID-19 on students studying abroad, with a focus on Chinese international students. He showed that Chinese international students faced significant levels of anxiety in the early stages of the COVID-19 pandemic, which was primarily caused by preconceived fear of COVID-19 and contradictory information often received from different sources.…”
Section: Discussionmentioning
confidence: 99%